Intangible Assets Pesantren : Kesesuaian Antara Citra dan Identitas Pesantren Dalam Mewujudkan Good Reputation - Firdaus Ainul Yaqin; Hambali Hambali; Fathor Rozi; Ahmad Muktashim Billah (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2023)
The purpose was to reveal the form of non-physical assets carried out by Islamic boarding schools as a step to adjust the image with the identity of the Islamic boarding school so that it can create a good reputation among the community. This research method used a qualitative case study type. Nurul Hikmah Pesisir Besuki Situbondo boarding school was the location and object of this research. Data collection techniques used observation, interviews with 5 informants (the caregivers, the head of the Islamic boarding school, and 2 community leaders), and documentation. The analysis technique applied the interactive analytical model of Miles, Huberman, and Saldana by condensing the data, presenting the data, which then draws conclusions. Source triangulation was a technique for checking the validity of data. The results of the study explained that the Nurul Hikmah Islamic boarding school had a fairly good reputation. There were several intangible assets in building this reputation, including (1) good and positive relations with community leaders. (2) the risk of crisis becomes smaller. (3) mutual understanding between target audiences, both internal (such as increasing the loyalty of pesantren staff) and externally. The pesantren management had a high commitment to carry out pesantren activities in accordance with what is stated in the vision and mission, and pays attention to crucial issues related to the routines carried out by the pesantren. This fact once again confirmed that the reputation of the pesantren is formed from the non-physical assets of the pesantren rather than physical assets.